Efficacy of electroacupuncture with different frequencies in the treatment of chemotherapy-induced peripheral neuropathy: A study protocol for a randomized controlled trial - Lu, Chao; Bao, Wenlong; Deng, Dehou; Li, Rongrong; Li, Guangliang; Zou, Shanlin; Wang, Yan (Frontiers in Neurology, 2022)
Introduction Chemotherapy-induced peripheral neuropathy (CIPN) is a common complication in patients with cancer during chemotherapy. It mainly leads to severe numbness of the hands and feet and causes great pain in patients. Electroacupuncture (EA) is considered to be beneficial in improving peripheral neuropathy and relieving numbness of the hands and feet. This trial aims to evaluate the therapeutic effect of different frequencies of EA on CIPN in patients with cancer. Methods and analysis This study is a randomized controlled trial. In total, 160 eligible CIPN patients are randomly assigned to the 2 Hz EA group, 100 Hz EA group, 2/100 Hz EA group, and control group in the ratio of 1:1:1:1. All patients in the EA treatment groups receive treatment with EA three times a week for 4 weeks and following up for 4 weeks. The patients in the control group are given Mecobalamin (MeCbl) tablets orally, one tablet at a time, three times a day, for 4 weeks, and following up for 4 weeks. The primary outcome measures are the participant neurotoxicity questionnaire (PNQ) and the peripheral neurotoxicity assessment rating (NCI CTCAE V5.0). Secondary outcomes are the quality of life scale (EORTC QLQ-C30) and the measurement of peripheral nerve conduction velocity (NCV). The results are evaluated at baseline, post-treatment phase, and following up for 4 weeks. All major analyses are based on the intention to treat principle. Ethics/dissemination This protocol was approved by the Medical Ethics Committee of the Cancer Hospital of the University of Chinese Academy of Sciences (Zhejiang Cancer Hospital) on 7 December 2021. The license number is IRB-2021-458. This study provides clinical efficacy data of different frequencies of EA in the treatment of CIPN. The results help to prove whether EA is an effective therapy for CIPN and optimize the frequency of EA for CIPN. The results of this study are shared with health care professionals, the public, and relevant organizations through the publication of manuscripts and conference reports. Trial registration number ChiCTR2100054458.